Pregões eletrônicos: a experiência brasileira e o estudo de caso de uma universidade do estado de Goiás - Dias, Sebastião Carlos (Universidade do Vale do Rio dos Sinos, 2023)
In this research, a detailed study was carried out on public biddings, electronic trading modality, in a Public University of the State of Goias. The central objective was to deepen the understanding of public tenders in the institution, with a specific focus on electronic trading, examining its most up-to-date practices in Brazil and in other countries. In addition, we sought to identify the general approaches adopted for conducting the electronic auction at the University, in order to assess its efficiency in obtaining percentage discounts on values during the acquisition of common goods that have similar characteristics. To achieve the proposed objectives, the research involved collecting data from all trading sessions held in the period from 2019 to 2021. Products with similar characteristics were grouped by areas to ensure comprehensive results and by sectors. Statistical analysis was used to interpret the collected data and, through this process, it was possible to achieve the results proposed for the study, however, these did not demonstrate economic efficiency in the processes. In this sense, it is essential that University A request a new survey to reassess and compare the results obtained, in order to implement measures aimed at improving bidding processes, especially electronic trading.
Keywords: Licitações públicas; Pregão eletrônico; Bens comuns; Public bids; Electronic auction; Common goods; ACCNPQ::Ciências Sociais Aplicadas::Administração